Yes, they can do it! Exploring female expatriates' effectiveness - Maria Bastida (European Research on Management and Business Economics (ERMBE), 2018)
Research has highlighted the under-representation of women in international assignments. While individual and organisational causes for this minor presence have been deeply explored, there is a lack of empirical studies on the effectiveness of female expatriates. Moreover, these studies have focused on a particular facet of effectiveness, and findings are usually based on the perceptions of women of their own work. Additionally, only a few of them include male expatriates, which undermine the possibility of making comparisons. This paper explores gender contingencies on expatriate effectiveness using different groups of measures: adjustment, premature return, performance, commitment and job satisfaction. The author carried out four logit models and, overall, and she did not found significant differences on effectiveness between female expatriates and men ones. Moreover, not-significant differences favour women. Theoretical and practical implications are contemplated.
Keywords: 650; Female expatriates; Women in IAs; Female effectiveness; Expatriate effectiveness